Amphiphilic Nanogels as Versatile Stabilizers for Pickering Emulsions - Cui, Ruiguang; Ickler, Maret; Markovina, Ante; Kanwal, Sidra; Vogel, Nicolas; Klinger, Daniel (ACS nano, 2024)
Pickering emulsions (PEs) are stabilized by particles at the water/oil interface and exhibit superior long-term stability compared to emulsions with molecular surfactants. Among colloidal stabilizers, nano/microgels facilitate emulsification and can introduce stimuli responsiveness. While increasing their hydrophobicity is connected to phase inversion from oil-in-water (O/W) to water-in-oil (W/O) emulsions, a predictive model to relate this phase inversion to the molecular structure of the nano/microgel network remains missing. Addressing this challenge, we developed a library of amphiphilic nanogels (ANGs) that enable adjusting their hydrophobicity while maintaining similar colloidal structures. This enabled us to systematically investigate the influence of network hydrophobicity on emulsion stabilization. We found that W/O emulsions are preferred with increasing ANG hydrophobicity, oil polarity, and oil/water ratio. For nonpolar oils, increasing emulsification temperature enabled the formation of W/O PEs that are metastable at room temperature. We connected this behavior to interfacial ANG adsorption kinetics and quantified ANG deformation and swelling in both phases via atomic force microscopy. Importantly, we developed a quantitative method to predict phase inversion by the difference in Flory-Huggins parameters between ANGs with water and oil (χwater - χoil). Overall, this study provides crucial structure-property relations to assist the design of nano/microgels for advanced PEs.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Flory−Huggins parameter; interfacial tension; nano/microgels; phase inversion; Pickering emulsions

Ethylene glycol/citric acid stabilized wet chemically synthesized Y2CoNiO6, and its structural, dielectric, magnetic and electrochemical behavior - Ickler, Maret; Devi, Manju; Rogge, Irina; Singh, Jashandeep; Kumar, Ashok (Journal of Materials Science: Materials in Electronics, 2020)
We report the synthesis of the novel double perovskite Y2CoNiO6 by an ethylene glycol and citric acid stabilized facile wet sol-gel chemical process. The material is iso-structural to the yttrium oxide cubic phase of Ia3 over bar symmetry (a = 10.5957 angstrom). The Raman vibrational modes at the wave numbers of 247, 489, 518, 566, 604, 649, 741 and 824 cm(-1) further confirmed the formation of Y2CoNiO6. The Y2CoNiO6 shows the room temperature dielectric constant of 5660 at the frequency of 500 Hz which increases further with the increase of temperature. It exhibits a predominant paramagnetic behavior with a second-order phase transition from antiferromagnetic to paramagnetic at the Neel temperature being T-FC = 51.65 K. The energy density of 19.97 W h kg(-1) at 1 A g(-1) and power density of 1324 W kg(-1) at 6 A g(-1) have been obtained. The effective charge storage is due to redox reaction of Co2+/Co3+ and Co3+/Co4+ as supported by X-ray photoelectron spectroscopy. The capacitance retainability of similar to 98.5% was achieved after 1200 charging/discharging cycles at 6 A g(-1).
CRIS-Team WoS Importer:2020-04-17

Interface-induced hysteretic volume phase transition of microgels: simulation and experiment - Kolker, Jannis; Harrer, Johannes; Ciarella, Simone; Rey, Marcel; Ickler, Maret; Janssen, Liesbeth M.C.; Vogel, Nicolas; Löwen, Hartmut (Soft Matter, 2021)
Thermo-responsive microgel particles can exhibit a drastic volume shrinkage upon increasing the solvent temperature. Recently we found that the spreading of poly(N-isopropylacrylamide) (PNiPAm) microgels at a liquid interface under the influence of surface tension hinders the temperature-induced volume phase transition. In addition, we observed a hysteresis behavior upon temperature cycling, i.e. a different evolution in microgel size and shape depending on whether the microgel was initially adsorbed to the interface in expanded or collapsed state. Here, we model the volume phase transition of such microgels at an air/water interface by monomer-resolved Brownian dynamics simulations and compare the observed behavior with experiments. We reproduce the experimentally observed hysteresis in the microgel dimensions upon temperature variation. Our simulations did not observe any hysteresis for microgels dispersed in the bulk liquid, suggesting that it results from the distinct interfacial morphology of the microgel adsorbed at the liquid interface. An initially collapsed microgel brought to the interface and subjected to subsequent swelling and collapsing (resp. cooling and heating) will end up in a larger size than it had in the original collapsed state. Further temperature cycling, however, only shows a much reduced hysteresis, in agreement with our experimental observations. We attribute the hysteretic behavior to a kinetically trapped initial collapsed configuration, which relaxes upon expanding in the swollen state. We find a similar behavior for linear PNiPAm chains adsorbed to an interface. Our combined experimental - simulation investigation provides new insights into the volume phase transition of PNiPAm materials adsorbed to liquid interfaces.
CRIS-Team WoS Importer:2021-05-28
Keywords: Responsive microgels; Soft particles; Temperature; Poly(n-isopropylacrylamide); Suspensions; Behavior; Water; Deformation; Adsorption; Dendrimers

Interfacial self-assembly of SiO2-PNIPAM core-shell particles with varied crosslinking density - Ickler, Maret; Menath, Johannes; Holstein, Laura; Rey, Marcel; Buzza, D. Martin A.; Vogel, Nicolas (Soft Matter, 2022)
Spherical particles confined to liquid interfaces generally self-assemble into hexagonal patterns. It was theoretically predicted by Jagla two decades ago that such particles interacting via a soft repulsive potential are able to form complex, anisotropic assembly phases. Depending on the shape and range of the potential, the predicted minimum energy configurations include chains, rhomboid and square phases. We recently demonstrated that deformable core-shell particles consisting of a hard silica core and a soft poly(N-isopropylacrylamide) shell adsorbed at an air/water interface can form chain phases if the crosslinker is primarily incorporated around the silica core. Here, we systematically investigate the interfacial self-assembly behavior of such SiO2-PNIPAM core-shell particles as a function of crosslinker content and core size. We observe chain networks predominantly at low crosslinking densities and smaller core sizes, whereas higher crosslinking densities lead to the formation of rhomboid packing. We correlate these results with the interfacial morphologies of the different particle systems, where the ability to expand at the interface and form a thin corona at the periphery depends on the degree of crosslinking close to the core. We perform minimum energy calculations based on Jagla-type pair potentials with different shapes of the soft repulsive shoulder. We compare the theoretical phase diagram with experimental findings to infer to which extent the interfacial interactions of the experimental system may be captured by Jagla pair-wise interaction potentials.
CRIS-Team WoS Importer:2022-07-29

Nanogels with tailored hydrophobicity and their behavior at air/water interfaces - Cui, Ruiguang; Ickler, Maret; Menath, Johannes; Vogel, Nicolas; Klinger, Daniel (Soft Matter, 2025)
The interfacial behavior of micro-/nanogels is governed to a large extent by the hydrophobicity of their polymeric network. Prevailing studies to examine this influence mostly rely on external stimuli like temperature or pH to modulate the particle hydrophobicity. Here, a sudden transition between hydrophilic and hydrophobic state prevents systematic and gradual modulation of hydrophobicity. This limits detailed correlations between interfacial behavior and network hydrophobicity. To address this challenge, we introduce a nanogel platform that allows accurate tuning of hydrophobicity on a molecular level. For this, via post-functionalization of active ester- based particles, we prepare poly(N-(2-hydroxypropyl)methacrylamide) (PHPMA) nanogels as a hydrophilic benchmark and introduce gradually varied amounts of hydrophobic propyl or dodecyl moieties to increase the nanogel hydrophobicity. We study the deformation and arrangement of these particles at an air/water interface and correlate the results with quantitative measures for nanogel hydrophobicity. We observe that increasing hydrophobicity of nanogels, either by increasing the hydrophobic moiety ratio or the alkyl chain length, leads to decreased particle deformability and aggregation of an interfacially-adsorbed monolayer. Contrary to what may be intuitively assumed, these changes are not gradual, but rather occur suddenly above a threshold in hydrophobicity. Our study further shows that the effect of hydrophobicity affects the nanogel properties differently in bulk and when adsorbed at liquid interfaces. Thus, this study establishes the transition of interfacial behavior between soft gel-like particles to a solid spherical morphology triggered by the increase in hydrophobicit
Keywords: Benchmarking; Chain length; Microgels; Monolayers; Nanoclay; Nanopores; Active esters; Air/Water Interfaces; External stimulus; Hydrophilic and hydrophobic; Interfacial behaviors; Molecular levels; Nanogels; Particle hydrophobicity; Polymeric networks; Postfunctionalization; Nanogels

Predictive design of plasmonic color - Bleyer, Gudrun; Uihlein, Andrian; Sultan, Umair; Ickler, Maret; Yamashita, Ruri; Pflug, Lukas; Watanabe, Satoshi; Vogel, Nicolas (Journal of Colloid and Interface Science, 2025)
Predictive design promises direct access to nanomaterials with optimal properties, identified by a rigorous mathematical optimization. This strategy thus provides structural blueprints for synthesis and eliminates extensive parameter screening. Here, we establish predictive design of nanoparticle systems using the example of plasmonic coloration. The perceived color of nanoparticle dispersions is influenced by the interplay of the entire visible particle spectrum with the wavelength-dependent sensitivities of the human eye, and not a mere function of plasmon resonances. We use Mie theory to compute the far-field spectra of spherical gold and silver core–shell nanoparticles and convert them into color perceived by the human eye. Color maps that describe the minimum color difference relative to a predefined target are established as a function of concentration, core diameter and shell thickness, thus providing predictions of the optimal particle structure for a targeted color. We demonstrate the feasibility of this predictive design by successfully targeting multiple colors and discuss limitations and discrepancies between experiment and simulations. Our results showcase that predictive design holds promise for resource-efficient syntheses of functional nanoparticles as the optimal structural blueprints for a desired target property can be accurately predicted in silic
Keywords: Plasmonic color; Predictive design; Nanoparticles; Structure optimization; CIElab

Soft Particles at Liquid Interfaces: From Molecular Particle Architecture to Collective Phase Behavior. - Ciarella, Simone; Rey, Marcel; Harrer, Johannes; Holstein, Nicolas; Ickler, Maret; Löwen, Hartmut; Vogel, Nicolas; Janssen, Liesbeth M. C. (Langmuir, 2021)
-isopropylacrylamide) particle systems using phase-contrast atomic force microscopy and correlate the distinct interfacial morphology with their bulk molecular architecture. We subsequently introduce a new coarse-grained simulation method that uses augmented potentials to translate this interfacial morphology into the resulting phase behavior upon compression. The main novelty of this method is the possibility to efficiently encode multibody interactions, the effects of which are key to distinguishing between heterostructural (anisotropic collapse) and isostructural (isotropic collapse) phase transitions. Our approach allows us to qualitatively resolve existing discrepancies between experiments and simulations. Notably, we demonstrate the first in silico account of the two-dimensional isostructural transition, which is frequently found in experiments but elusive in simulations. In addition, we provide the first experimental demonstration of a heterostructural transition to a chain phase in a single-component system, which has been theoretically predicted decades ago. Overall, our multiscale framework provides a phenomenological bridge between physicochemical soft-particle characteristics at the molecular scale and nanoscale and the collective self-assembly phenomenology at the macroscale, serving as a stepping stone toward an ultimately more quantitative and predictive design approach.

Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya Sukumar; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10